Reliability constrained multi-commodity dispatch in restructured power systems - Liu, Yong (2008)
Nowadays, significant changes have occurred in power industries. The traditional vertically integrated electric utility structure has been unbundled and economically separated into generation companies, transmission companies and distribution companies. This process is called restructuring or deregulation. Electric utility restructuring has brought forth significant changes in power system operation, planning, and trading process. In this new environment, many new topics are brought forward for academic researchers. Particularly, maintaining and/or enhancing power system reliability in the new environment has become one of the most important topics, which is the subject of this thesis. This thesis is to investigate the technique to settle the energy and ancillary services to keep the system reliability at the required and appropriate level. A bi-fold approach is adopted to achieve this goal. On one hand, interruptible load (IL) is introduced as a source of operational reserve for the reliable operation of a restructured power system. On the other hand, the reliability-constrained system reserve criterion is proposed and used as a constraint in the day-ahead electricity market settlement, which can more accurately assess the system operational risk and set the system reserve requirement accordingly. Furthermore, the impact of interruptible load, different system reserve criteria, and the transmission system failures on electricity market settlement has been investigated.